2019
DOI: 10.1096/fj.201901106r
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin deficiency does not induce macrophagic iron overload: lessons from a new rat model of hereditary aceruloplasminemia

Abstract: Hereditary aceruloplasminemia (HA), related to mutations in the ceruloplasmin (Cp) gene, leads to iron accumulation. Ceruloplasmin ferroxidase activity being considered essential for macrophage iron release, macrophage iron overload is expected, but it is not found in hepatic and splenic macrophages in humans. Our objective was to get a better understanding of the mechanisms leading to iron excess in HA. A clustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPR associated protein 9 (Cas9) kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Since macrophages are key cells in iron recycling, a macrophage iron overload would be expected in ACP. Conversely, iron accumulation is usually observed in hepatocytes/liver ( Figure 1) rather than in macrophages/spleen in affected patients, suggesting that additional pathophysiologic roles of CP are probably involved [17]. Specifically, it has been reported that GPI-anchored CP can also modulate the interaction between ferroportin and hepcidin [18][19][20], the master regulator of systemic iron homeostasis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since macrophages are key cells in iron recycling, a macrophage iron overload would be expected in ACP. Conversely, iron accumulation is usually observed in hepatocytes/liver ( Figure 1) rather than in macrophages/spleen in affected patients, suggesting that additional pathophysiologic roles of CP are probably involved [17]. Specifically, it has been reported that GPI-anchored CP can also modulate the interaction between ferroportin and hepcidin [18][19][20], the master regulator of systemic iron homeostasis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, Cu in the bloodstream is also bound to proteins other than ceruloplasmin and potentially also to non-protein molecules. Humans and mice with no ceruloplasmin in the circulation survive fairly well overall, although not without some complications involving both Cu and Fe metabolism [54][55][56][57]. In Wilson disease (with no functional ATP7B to incorporate Cu into ceruloplasmin), there still is Cu in the blood, and subjects lead relatively normal lives as long as they are treated with chelators to remove the excess Cu [3].…”
Section: Forms Of Cu In Other Gi Fluids and Their Originsmentioning
confidence: 99%
“…Hereditary aceruloplasminemia is a genetic disease characterized by progressive iron overload (liver and brain) and is related to mutations in the ceruloplasmin (CP) gene. In contrast to Cp KO mice, Cp KO rats mimic the human phenotype with hepatosplenic iron load and could be more appropriate for providing information to understand and treat the disease (Kenawi et al, 2019).…”
Section: Metabolic Diseasesmentioning
confidence: 99%